Kalirin-RAC controls nucleokinetic migration in ADRN-type neuroblastoma - Afanasyeva, Elena; Gartlgruber, Moritz; Ryl, Tatsiana; Decaesteker, Bieke; Denecker, Geertrui; Mönke, Gregor; Toprak, Umut; Flórez, Andrés; Torkov, Alica; Dreidax, Daniel; Herrmann, Carl; Okonechnikov, Konstantin; et al. (Life science alliance, 2021)
The migrational propensity of neuroblastoma is affected by cell identity, but the mechanisms behind the divergence remain unknown. Using RNAi and time-lapse imaging, we show that ADRN-type NB cells exhibit RAC1- and kalirin-dependent nucleokinetic (NUC) migration that relies on several integral components of neuronal migration. Inhibition of NUC migration by RAC1 and kalirin-GEF1 inhibitors occurs without hampering cell proliferation and ADRN identity. Using three clinically relevant expression dichotomies, we reveal that most of up-regulated mRNAs in RAC1- and kalirin-GEF1-suppressed ADRN-type NB cells are associated with low-risk characteristics. The computational analysis shows that, in a context of overall gene set poverty, the upregulomes in RAC1- and kalirin-GEF1-suppressed ADRN-type cells are a batch of AU-rich element-containing mRNAs, which suggests a link between NUC migration and mRNA stability. Gene set enrichment analysis-based search for vulnerabilities reveals prospective weak points in RAC1- and kalirin-GEF1-suppressed ADRN-type NB cells, including activities of H3K27- and DNA methyltransferases. Altogether, these data support the introduction of NUC inhibitors into cancer treatment research.
Gesehen am 19.08.2021